Insights into the biodiversity of the gut microbiota of broiler chickens. (27th June 2016) - Mancabelli, Leonardo; Ferrario, Chiara; Milani, Christian; Mangifesta, Marta; Turroni, Francesca; Duranti, Sabrina; Lugli, Gabriele Andrea; Viappiani, Alice; Ossiprandi, Maria Cristina; van Sinderen, Douwe; Ventura, Marco
Summary: The gastrointestinal tract of poultry is densely populated with microorganisms, which are presumed to interact with the host and ingested feed. Comparison of the gut microbiota of chickens used for large‐scale commercial production (Broiler Chicken, BC) and those grown in semi‐wild conditions (Free‐Range Chicken, FRC) revealed that at phylum level Firmicutes was the dominant phylum of the gut community in BC, while the gut microbiota of FRC contained higher levels of Bacteroidetes and Proteobacteria . Such differences may be due to the diet and/or the intensive use of antibiotics in BC. Indeed, analysis of the resistome of the cecal microbiomes showed a marked richness in BC datasets, with a modulation of the cecal microbiota toward antibiotic resistant bacteria. Functional characterization of the microbiome of FRC samples revealed an increase in gene pathways involved in degradation of complex carbohydrates. Furthermore, in silico analyses of the microbiomes of FRC and BC revealed a higher presence in genes involved in formate production in BC samples. Notably, compared to the BC microbiomes the FRC microbiomes were shown to contain a higher abundance of genes involved in the pathway for acetate production.